Online Learning Model Based on Learning Management System to Support Student Exchange Program - Markus Deli Girik Allo; Elim Trika Sudarsi; Nilma Taula’bi’; Eka Prabawati Rum (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this study is to reveal EFL Lecturers' perception of Learning Management Systems (LMS) for Online Learning, to investigate characteristics of the approach used by the lecturer in LMS-based Online Learning, to overview the impact of the implementation of LMS-based online learning on students' affective, behavioral, and cognitive aspects, and to depict the LMS-SPADA-based online learning model used by lecturers in student exchange programs. Researchers applied qualitative methods with ethnographic design. The subjects of this study were 9 lecturers and 23 students. Data collection in this study used observation and interview techniques.  The data analysis technique used is transcription, coding, and thematic analysis.  The result of this study confirms that EFL Lecturers' perceptions of LMS for Online Learning are (1) strongly supportive of LMS for online learning; (2) fairly supportive of LMS for online learning; and (3) weakly supportive of LMS for online learning. The approach used by the lecturer in LMS-based Online Learning is characterized by applying a student-centred view in LMS-based Online Learning.